Speech and language sequelae of severe malaria in Kenyan children. - Carter, J; Murira, G; Ross, A; Mung'ala-Odera, V; Newton, C (2003)
PRIMARY OBJECTIVE: To conduct a preliminary investigation into the occurrence of speech and language impairments following severe malaria in Kenyan children. RESEARCH DESIGN: Cohort study comparing the prevalence of impairments in children exposed or unexposed to severe malaria. METHODS AND PROCEDURES: The study recruited 25 children who had previously been admitted to hospital with severe falciparum malaria and 27 unexposed to the disease. Assessments of comprehension, syntax, lexical semantics, higher level language abilities, pragmatics and phonology were administered to each child at 8-9 years of age, at least 2 years after admission to hospital in children exposed to severe malaria. MAIN OUTCOMES AND RESULTS: Exposed children were found to have lower scores on each assessment and significantly lower scores on four aspects of language ability: comprehension (p = 0.02); syntax (p = 0.02); content words (p = 0.02) and function words (p = 0.004) components of lexical semantics. CONCLUSIONS: These data suggest that speech and language deficits may be an important and under-recognized sequela of severe falciparum malaria.